Measuring recovery in opioid use disorder: clinical utility and psychometric properties of the Treatment Effectiveness Assessment - Ling W; Nadipelli VR; Solem CT; Farabee D; Ronquest NA; Perrochet B; Learned SM; Deshpande CG; Heidbreder C (Dove Medical Press, 2019)
Walter Ling,1 Vijay R Nadipelli,2 Caitlyn T Solem,3 David Farabee,1,4 Naoko A Ronquest,2 Brian Perrochet,1,5 Susan M Learned,6 Chinmay G Deshpande,3 Christian Heidbreder71UCLA Department of Family Medicine, Center for Behavioral and Addiction Medicine, Los Angeles, CA, USA; 2Global Health Economics and Outcomes Research, Indivior Inc, Richmond, VA, USA; 3Patient-centered outcomes Center of Excellence, Pharmerit International, Bethesda, ML, USA; 4Department of Population Health, School of Medicine,, New York, NY, USA; 5Marron Institute of Urban Management, Marron Institute, New York University, New York, NY, USA; 6Global Medicines Development, Indivior Inc, Richmond, VA, USA; 7Global Research and Development, Indivior Inc, Richmond, VA, USAPurpose: The Treatment Effectiveness Assessment (TEA) is a patient-centered instrument for evaluating treatment progress and recovery from substance use disorders, including opioid use disorder (OUD). We assessed the TEA’s reliability and validity and determined minimal clinically important differences (MIDs) in participants with moderate to severe OUD.Patients and methods: The TEA measures change in four single-item domains (substance use, health, lifestyle, community involvement) from treatment initiation across the duration of a treatment program. Self-reported responses range from 1 (“none or not much”) to 10 (“much better”) with items summed to a total score ranging from 4–40. We assessed floor and ceiling effects, internal consistency, test-retest reliability, known-groups validity (ANOVA stratified by current health status [36-Item Short Form Health Survey item 1]), convergent/divergent validity, and MIDs using data from a phase 3, open-label clinical trial of buprenorphine extended-release monthly injection for subcutaneous use (BUP-XR). Participants with OUD completed the TEA at screening and before monthly injections for up to 12 months.Results: Among 410 participants (mean age 38 years; 64% male), the mean baseline (pre-injection 1) TEA total score was 25.4 (SD 9.7), with <10% of participants at the measure floor and 10%–20% at the ceiling across domains. Internal consistency was high (Cronbach’s α=0.90), with marginal test-retest reliability (intraclass correlation coefficient =0.69). Mean TEA total score consistently increased from baseline (n=410; mean 25.4 [SD 9.7]) to end of study (n=337; 35.0 [6.7]) and differentiated between current health status groups (P<0.001); it was weakly correlated with other measures of health-related quality of life/severity. MIDs ranged from 5–8 for the TEA total score across anchor- and distribution-based approaches.Conclusion: The TEA exhibited acceptable reliability and validity in a cohort of participants with moderate to severe OUD treated with BUP-XR. Given its brevity and psychometric properties, the TEA is a promising tool for use in clinical practice and research.Keywords: Treatment Effectiveness Assessment, TEA, opioid use disorder, patient-reported outcomes, addiction, psychometrics